Women's Roles in Adding Value to Wooden Crafts and Contributing to Family Income in Babung, Gunungkidul - Slamet Subiyantoro (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2021)
Gender discrimination continues to exist in the Special Region of Yogyakarta, with women often placed in the role of mother and housekeeper. In areas such as Bobung Village, where they form an integral part of the local industry, women transcend these roles to contribute to the economy. This research aimed to examine women's roles in adding to the artistic value of wooden crafts, their impact on increasing family income, and local community members’ views towards these female roles. The research was socio-anthropological, with data obtained through in-depth interviews, participant observations, and content analyses of documents and records. Data were analyzed using an interactive model including data collection, reduction of presentation, and verification. The findings showed that (1) women play a significant role in improving the artistic value of wooden crafts through their batik painting and writing techniques. They make these crafts appear more exotic, and help to preserve traditional batik motifs. (2) With the addition of these women’s motifs to wooden crafts, they add to their family income while still performing their domestic duties, such as caring for their children and cooking. Their wages are based on a daily system, collective system, or combination of both. (3) Batik-making on wooden crafts has feminine characteristics; it is soft and light, as opposed to woodworking’s masculine characteristics of hard, physical work. Women’s batik-making is consequently complementary to the work performed by men. According to the local people, there is no gender bias related to the job differentiation between men and women.